Constraining sleptons at the LHC in a supersymmetric low-scale seesaw scenario - Cerna-Velazco N. (2017)
This work has been supported by BAYLAT, project nr. 914-20.1.1. T.F. and W.P. have been supported by the DFG, project nr. PO-1337/3-1. J.J.P. acknowledges funding by the Dirección de Gestión de la Investigación at PUCP, through grant DGI-2015-3-0026. N.C.V. has been supported by CienciActiva-CONCYTEC Grant 026-2015. We also acknowledge the financial support of PUCP DARI Groups Research Fund 2016. We would especially like to thank O. A. Díaz in the Dirección de Tecnologías de Información at PUCP, for implementing the code within the LEGION system.